Isokinetic exercise velocities and blood lactate concentrations in strength/power and endurance athletes - Regan, W. F.; Potteiger, J. A. (The Journal of Strength and Conditioning Research, 1999)
We examined the effect of different isokinetic exercise velocities on blood lactate concentration in strength/power (SP) and endurance (EN) athletes. Ten SP athletes (96.8 ± 16.2 kg) and 10 EN athletes (70.1 ± 9.4 kg) performed 20 maximal isokinetic knee extensions and flexions at 3 velocities (1.05, 2.09, and 5.23 rad·s1) on an isokinetic dynamometer. Trials were randomly assigned and separated by at least 48 hours. Capillary blood samples (150 l) were collected before and 2, 4, and 6 minutes after exercise. Significant differences were observed for blood lactate concentrations among velocities for SP athletes with postexercise values at 1.05 rad·s1 (2 minutes, 6.64 ± 0.46; 4 minutes, 6.87 ± 0.50; 6 minutes, 6.34 ± 0.39 mmol·L1) and 2.09 rad·s1 (2 minutes, 6.49 ± 0.30; 4 minutes, 6.57 ± 0.34; 6 minutes, 6.67 ± 0.45 mmol·L1) higher than 5.23 rad·s1 (2 minutes, 5.40 ± 0.30; 4 minutes, 5.46 ± 0.33; 6 minutes, 5.40 ± 0.32 mmol·L1). No significant difference was observed in blood lactate concentrations among velocities for EN. The postexercise blood lactate concentrations were significantly higher for SP athletes compared with EN athletes at each velocity; however, this difference was eliminated when corrected for body mass. Total work was significantly greater for SP athletes compared with EN athletes at each velocity. Total work performed by both SP and EN athletes was significantly higher at 1.05 and 2.09 rad·s1 compared with 5.23 rad·s1. The data indicate that SP athletes will produce the highest blood lactate concentrations when using slower isokinetic velocities, which may be due to the total amount of work performed.